Bambusa vulgaris: A comprehensive review of its traditional uses, phytochemicals and pharmacological activities (Sciences of Phytochemistry, 2022)
A versatile plant with many purposes, Bambusa vulgaris is primarily known for its industrial applications, but it is also becoming acknowledged as a possible source of bioactive substances and as a functional food. Every component of the bamboo plant, including the rhizome, culm shavings, leaves, roots, shoots, and seeds, has potential medical uses. This review aims to provide an insight into the traditional uses, and the various pharmacological activities exhibited by B. vulgaris extracts like analgesic, antihyperglycemic, antipyretic, anti-inflammatory, antioxidant, antimicrobial, antiviral, hepatoprotective, anti-amnesic, etc. It also has immense potential to be used as an important functional food as it has a high content of useful proteins, carbohydrates, high fiber content, and very low fat.